Efficacy and safety of minodronic acid hydrate in patients with steroid‐induced osteoporosis. (1st March 2016) - Kitamura, Noboru; Shiraiwa, Hidetaka; Inomata, Hirotake; Nozaki, Takamasa; Ikumi, Natsumi; Sugiyama, Kaita; Nagasawa, Yousuke; Karasawa, Hiromi; Iwata, Mitsuhiro; Matsukawa, Yoshihiro; Takei, Masami
Abstract: Objectives: Minodronic acid hydrate, an oral bisphosphonate, has a greater inhibitory effect on bone resorption than do other approved drugs; however, this has been studied only in patients with primary osteoporosis. Here, we administered minodronic acid hydrate to patients with steroid‐induced osteoporosis who have been treated with steroids for rheumatoid arthritis or other collagen diseases, and the efficacy and safety of minodronic acid hydrate were prospectively investigated. Methods: Twenty‐five patients treated in our rheumatology clinic received minodronic acid hydrate 1 mg/day. The changes in bone mineral density (BMD) and bone turnover markers were investigated at 3 and 6 months, and adverse events, including the presence or absence of an incident osteoporotic fracture, were examined over a period of 6 months. Results: Percent changes in BMD of the lumbar spine and femur significantly increased. The values of bone turnover markers significantly decreased. There were no patients with a radiographically apparent incident fracture. Adverse events included toothache for which the patient discontinued the treatment and three cases of gastrointestinal disorder that did not lead to discontinuation, and thus minodronic acid hydrate was well tolerated. Conclusions: Here, we show that minodronic acid hydrate is effectively and safely used for treatment of steroid‐induced osteoporosis.